The content analysis methodology. Uses and applications in communication research on Spanish-speaking countries - Valeriano Piñeiro-Naval (Communication & Society (Formerly Comunicación y Sociedad), 2020)
Based on a conceptual review of the content analysis research method, this article identifies meta-research studies that confirm the relevance of this technique in the atomised field of communication sciences. In light of the empirical evidence, this study is based on an analysis of 262 papers that use this tool and were published in major Spanish-language journals between 2013 and 2017. At instrumental level, bibliometric exploration is combined with content analysis itself, considering 18 categories, such as authorship, funding, sampling method and reporting of intercoder reliability. The results indicate that there is a steady annual growth in the number of papers produced by researchers affiliated to Spanish universities. These papers have more than two authors on average and often lack additional financial resources. As for the implementation of the content analysis method, it is generally applied to non-probabilistic samples and does not involve any intercoder reliability assessment and reporting. A series of recommendations are offered for researchers in Spain and in Latin America to meet international standards.